Ace in the hole: media panics, muted voices, and anxieties of consumption in the reception of Joker. Issue 1 (2nd January 2021) - Mathijs, Ernest
ABSTRACT: This essay contrasts components of the reception of Joker : the media panic which accompanied its release, the muted reception following its theatrical and home-viewing releases, and its anxious reception contexts. These processes showcase how Joker 's reception became 'normalized', neutered and made to fit into categories of mediated debate dictated by standards of public discourse from which many potential participants felt shut out – or, not unlike Arthur Fleck (Joaquin Phoenix) in the film, relegated to 'Late Late Show' fall guy appearances.